2019
DOI: 10.1098/rsta.2018.0441
|View full text |Cite
|
Sign up to set email alerts
|

The Ramanujan conjecture and its applications

Abstract: In this paper, we review the Ramanujan conjecture in classical and modern settings and explain its various applications in computer science, including the explicit constructions of the spectrally extremal combinatorial objects, called Ramanujan graphs and Ramanujan complexes, points uniformly distributed on spheres, and Golden-Gate Sets in quantum computing. The connection between Ramanujan graphs/complexes and their zeta functions satisfying the Riemann hypothesis is also discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Finally, another interesting hint to a connection with number theory: Ihara defined the notion of Zeta function of a k-regular graph X, and Sunada observed that X is Ramanujan if and only if this Zeta function satisfies 'the Riemann hypothesis'. We refer the reader to the survey [11] for more details.…”
Section: Why Ramanujan?mentioning
confidence: 99%
“…Finally, another interesting hint to a connection with number theory: Ihara defined the notion of Zeta function of a k-regular graph X, and Sunada observed that X is Ramanujan if and only if this Zeta function satisfies 'the Riemann hypothesis'. We refer the reader to the survey [11] for more details.…”
Section: Why Ramanujan?mentioning
confidence: 99%